The Politics of Victimhood Representation in True Story-Based Films: A Conceptual Analysis of Indonesia and the United States - Annisah Putri; Rizfa Maghfirah; Zakirah Azman (Jurnal Soshum Insentif, 2026)
This article examines the politics of victimhood representation in true story-based films through a conceptual comparison between Indonesia and the United States. It argues that portrayals of female victims are not merely narrative choices but are shaped by media regimes, policy frameworks, and socio-cultural contexts that influence how gender-based violence is understood publicly. Using Vina Sebelum 7 Hari and She Said as illustrative cases, the study identifies two contrasting patterns of victimhood representation: sensational victimhood, which emphasizes suffering and emotional spectacle, and advocacy victimhood, which connects victims’ experiences to institutional accountability and justice processes. The analysis suggests that these representational differences have political implications for public perceptions of gender-based violence, the normalization of accountability, and the effectiveness of protection policies. By linking media representation with gender governance, this study highlights the role of film as a symbolic arena that shapes public understanding of justice, responsibility, and women’s rights in different socio-political contexts.